A differential delay line for optical coherence domain polarimetry. (20th February 2015) - Li, C; Yang, J; Yuan, Y G; Zhou, A; Yan, D K; Chai, J; Liang, S; Hou, L; Wu, B; Peng, F; Zhang, Y; Liu, Z H; et al.
Abstract: We propose an optical delay line based on differential structure for improving measurement accuracy and extending scanning length of optical coherence domain polarimetry (OCDP). The differential delay line is composed of two independent graded refractive index lenses (GRIN) and a double-faced mirror. The OCDP measurement model with loss coefficient and measurement error caused by the GRIN-lens-based delay line is discussed. Compared to the general optical delay line based on a single GRIN lens, the fluctuation of the loss coefﬁcient of differential delay line is reduced to ± 0.1 dB with scanning range of 0.8 m, which corresponds to 80% improvement.